A study on using short stories in teaching reading skill at Nguyen Khuyen secondary school: M.A Thesis Linguistics: 60 14 01 11 - Phạm, Lan Anh (ĐHNN, 2017)
Reading comprehension has been highlighted as a problem among secondary school students. This study examined the effects of short stories on 80 seven grade students to show if the method had an impact on students’ reading comprehension. Besides, this research also figured out the suitable methods teachers used to exploit short stories in teaching reading skill. To serve this purpose, some instruments were used: pretest, posttest; questionnaire for teachers and questionnaire for students. Although the findings revealed some limitations, the use of short stories helped students to improve their reading comprehension. The result in reading test showed a slight improvement on the students‟ average score. In addition, the result from questionnaire and interview indicated both teachers and students had difficulties when teaching and learning reading through short stories. However, many suitable methods had been applied to help students and teachers overcome these obstacles and ensure the better use of short stories in teaching reading skill. It is thus recommended for further studies to minimize the challenge found in this study and vary kinds of short stories used in teaching English skills.